2021
DOI: 10.1093/scipol/scab032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating blockchain technology and related policies in China and the USA

Abstract: Blockchain has been regarded as an emerging global technological phenomenon. This study uses the patent analysis method to compare the development of blockchain technology in China and the USA. An overview of blockchain policies in China and the USA is presented. Our analyses suggest that policies related to the blockchain stimulate the number of blockchain patent applications and create regional innovation in China. The innovation capability of Chinese enterprises has been more affected by these policies than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…According to the verifiable data till the end of the 2020 exhibit, China had 1309 firms providing BCT services and more than 80 BCT research centers; there are exceeding 1189 Chinese BCT-related research papers published, and the number of patent applications in China exceeded 30,000; these data are all leading in the world (Cai et al, 2021). Furthermore, developing BCT strategy has become a national policy in today's China; as early as the end of 2016, BCT was mentioned as a strategic frontier technology in the 13th Five-Year Plan on National Informatization of China and continuously included in the latest 14th Five-Year Plan (Jiang et al, 2021); Chinese government and technology companies have tried to publicly launch the first state-sponsored BCT-based service platform, which is for removing the biggest roadblock of corporate BCT development-BCT-based service platform is expensive (Stockton, 2020). There are also thousands of online to offline conferences to broadcast and discuss the BCT development in Chinese industrial and academic area; top management and operation managers universally understand BCT development in today's Chinese manufacturing industry; even they have not used BCT in their companies.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…According to the verifiable data till the end of the 2020 exhibit, China had 1309 firms providing BCT services and more than 80 BCT research centers; there are exceeding 1189 Chinese BCT-related research papers published, and the number of patent applications in China exceeded 30,000; these data are all leading in the world (Cai et al, 2021). Furthermore, developing BCT strategy has become a national policy in today's China; as early as the end of 2016, BCT was mentioned as a strategic frontier technology in the 13th Five-Year Plan on National Informatization of China and continuously included in the latest 14th Five-Year Plan (Jiang et al, 2021); Chinese government and technology companies have tried to publicly launch the first state-sponsored BCT-based service platform, which is for removing the biggest roadblock of corporate BCT development-BCT-based service platform is expensive (Stockton, 2020). There are also thousands of online to offline conferences to broadcast and discuss the BCT development in Chinese industrial and academic area; top management and operation managers universally understand BCT development in today's Chinese manufacturing industry; even they have not used BCT in their companies.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Denter used the number of global blockchain patent applications as an indicator and found that Asian countries drive blockchain inventions (Denter, 2021). Jiang used patent analysis to compare the development of blockchain technology in China and the USA and found that the technology trends are the same (Jiang et al, 2021). Ozcan found that China and the USA have the potential to influence the future development of blockchain technology (Ozcan & Unalan, 2020).…”
Section: Introductionmentioning
confidence: 99%